Memory and history in social networks: new supports to resisting the forgetting of the Spanish Civil War and Francoism - Eiroa San Francisco, Matilde (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Social networks have an increasingly significant role in our daily lives, from superficial aspects to more relevant topics, such as the transmission of present and past values to contemporary society. One of their most original roles is that of becoming a support and record of recent history and memory, that is to say, brief virtual spaces which act as new ways of resisting that traumatic or little-known episodes are forgotten. This article intends to analyze said phenomenon taking the Spanish Civil War and the posterior Francoism as an example, with the objective of learning how they fulfill their function of generating, spreading and representing the resistance against forgetting. Methods of digital research were applied as well as sources from digital databases.